Developing an Integrated Conceptual Framework of Digital Leadership, Digital Organizational Culture, and School Digitalization: A Literature Review - Ahmad Nur Ismail; M. Triono Al Fata; Heri Cahyono Putro; Ahmad Pramudiyanto; Nanang Qosim (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
Digital transformation has reshaped the governance of educational organizations and heightened the demand for leadership capable of steering technology-driven change. However, studies examining the relationship between digital leadership, digital organizational culture, and school digitalization remain fragmented, lacking an integrated conceptual framework. This study aims to analyze the conceptual development of digital leadership in educational leadership literature, identify the role of digital organizational culture in supporting school digitalization, and synthesize the interrelationships among these constructs into an integrated conceptual framework. Employing a conceptual literature review approach across four stages literature identification, selection, qualitative coding and thematic synthesis, and conceptual framework development the research analyzed 46 articles meeting inclusion criteria. Qualitative content analysis using open, axial, and selective coding was conducted. Key findings indicate that digital leadership has evolved as a multidimensional construct encompassing digital vision, change management, digital competence, and organizational innovation. Furthermore, digital organizational culture functions as a strategic mechanism fostering values of innovation, collaboration, adaptability, and continuous learning to support school digitalization implementation. The synthesis yields the Digital Leadership, Digital Organizational Culture, and School Digitalization (LD-C-DS) Conceptual Framework, positing school digitalization as an outcome shaped by digital organizational culture, which is itself influenced by digital leadership practices. This study contributes to educational management and leadership scholarship by providing a conceptual foundation for future empirical research and digital transformation policy development in school settings.